Unproductive activities and the rate of surplus value at the industry level in Korea, 1995-2015 - Dong-min Rieu; Hyun Woong Park (University of Massachusetts, Department of Economics, 2018)
In order to explain how the Korean economy underwent the structural change through the two crises of 1997-8 and 2008 within the context of globalization, this article focuses on class analysis and inter-sectoral value transfer by estimating the sectoral rates of exploitation along with the sectoral monetary expressions of labor time. Our data indicate the possibility that the expansion of unproductive activities, accompanied by intensification of exploitation within the unproductive sectors, might not have overtaken capital accumulation in Korea during 1995-2015. It can also be concluded that the condition for manufacturing's capital accumulation steadily improved since the 1997-8 crisis, but started to deteriorate after 2011. Our value-theoretic analysis provides a foundation for understanding the context of the regime change, which may plausibly characterize the Korean economy last couple of decades.
Keywords: B51; 330; Sectoral rates of surplus value; unproductive labor; monetary expression of labor time; Korean economy